Missing pieces [compact disc, unabridged] - Gudenkauf, Heather (Brilliance Audio, 2016)
Sarah Quinlan's husband, Jack, has been haunted for decades by the untimely death of his mother when he was just a teenager, her body found in the cellar of their family farm, the circumstances a mystery. The case rocked the small farm town of Penny Gate, Iowa, where Jack was raised, and for years Jack avoided returning home. But when his beloved aunt Julia is in an accident, Jack and Sarah are forced to confront the past that they have long evaded. Caught in a flurry of unanswered questions, Sarah dives deep into the puzzling rabbit hole of Jack's past. But the farther in she climbs, the harder it is for her to get out. And soon she is faced with a deadly truth she may not be prepared for.